History in Mathematics Education - a study of research published in Brazil in the last five years História na Educação Matemática - um estudo sobre trabalhos publicados no Brasil nos últimos cinco anos - Romélia Mara Alves Souto (Universidade Estadual Paulista, 2010)
In this paper we report a study on research in the field of History in Mathematics Education conducted in Brazil in the last five years. We evaluate studies that are theoretical or report experiences on the support found in history that can contribute to the situations of teaching and learning of mathematics, based on the Proceedings of Seminários Nacionais de História da Matemática and Encontros Luso-Brasileiros de História da Matemática. Examining the interests, directions and focus of research in the field, we found that the vast majority of studies address specific issues of History of Mathematics, and the number of studies on History in Mathematics Education is still very low. We note that, in the last five years, the arguments in favor of the teaching potential of the History of Mathematics, which is very present in the speech of teachers and managers of public education, has not yet been materialized in experiments or investigations to promote this link effectively. Keywords: Mathematics Education. History of Mathematics. History in Mathematics Education. Neste artigo, relatamos um estudo sobre os trabalhos no campo da História na Educação Matemática, realizados no Brasil, nos últimos cinco anos. Avaliamos os estudos que fazem reflexões teóricas ou relatam experiências sobre o possível apoio da História em situações de ensino-aprendizagem da Matemática, com base nos Anais dos Seminários Nacionais de História da Matemática e dos Encontros Luso-Brasileiros de História da Matemática. Analisando os interesses, direções e focos das pesquisas no campo considerado, constatamos que a grande maioria dos trabalhos contempla temas específicos de História da Matemática e que o número de trabalhos sobre História na Educação Matemática ainda é pouco expressivo nos eventos em questão. Verificamos que, nos últimos cinco anos, a defesa das potencialidades didáticas da História da Matemática, há muito veiculada pelos discursos de professores, autores de livros didáticos e gestores da educação pública, ainda não se materializou em experiências ou investigações que promovam efetivamente essa articulação. Palavras-chave: Educação Matemática. História da Matemática. História na Educação Matemática.